Defect in BrMS1, a PHD-finger transcription factor, induces male sterility in ethyl methane sulfonate-mutagenized Chinese cabbage (Brassica rapa L. ssp. pekinensis) - Dong, Shiyao; Zou, Jiaqi; Fang, Bing; Zhao, Ying; Shi, Fengyan; Song, Gengxing; Huang, Shengnan; Feng, Hui (Frontiers in Plant Science, 2022)
Male sterility is an ideal character for the female parent in commercial hybrid seed production in Chinese cabbages. We identified three allele male sterile mutants msm2-1/2/3 in progenies of ethyl methane sulfonate (EMS)-mutagenized Chinese cabbage. It was proved that their male sterilities were controlled by a same recessive nuclear gene. Cytological observation showed that the delayed tapetal programmed cell death (PCD) as well as the abnormal pollen exine and intine led to pollen abortion in these mutants. MutMap combined with KASP analyses showed that BraA10g019050.3C, a homologous gene of AtMS1 encoding a PHD-finger transcription factor and regulated pollen development, was the causal gene. A single-nucleotide mutation from G to A occurred at the 2443th base of BrMS1 in msm2-1 which results in premature termination of the PHD-finger protein translation; a single-nucleotide mutation from G to A existed at 1372th base in msm2-2 that makes for frameshift mutation; a single-nucleotide mutation from G to A distributed at 1887th base in msm2-3 which issues in the amino acid changed from Asp to Asn. The three allelic mutations in BrMS1 all led to the male sterile phenotype, which revealed its function in stamen development. qRT–PCR analysis indicated that BrMS1 specially expressed in the anther at the early stage of pollen development and its expression level was higher in msm2-1/2/3 than that in the wild-type ‘FT’. BrMS1 was located at the nucleus and a length of 12 amino acid residues at the C-terminus had transcriptional activation activity. RNA-seq indicated that the mutation in BrMS1 affected the transcript level of genes related to the tapetum PCD and pollen wall formation, which brought out the pollen abortion. These male sterile mutants we developed provided a novel gene resource for hybrid breeding in Chinese cabbage.